Improving pasture resources in West Africa: Evaluation of forage legumes to meet the social and ecological constraints - Tarawali, Shirley A.; Peters, Michael; Mohamed-Saleem, M.A. (French Grassland Society, 1989)
Discusses six stages used in the evaluation of forage legumes conducted to select accessions that meet the social and ecological constraints in the subhumid zone of West Africa.